Flood Evacuation in Informal Settlements: Application of an Agent-Based Model to Kibera Using Open Data - Olivia Butters; Richard J. Dawson (Urban Science)
Flood incident management involves taking actions to save lives and reduce damages during a flood. Agent-based modelling tools have recently been developed to simulate the dynamic interactions between people and floodwater as a flood event unfolds. To date, these have only been applied in locations with a wealth of data, relying upon bespoke local or national datasets. Although informal settlements have a concentration of vulnerable people and are often more exposed to natural hazards, data availability is often limited, posing challenges for planning and implementing flood incident management actions. In this study, a model that was first applied in the UK is adapted and applied to simulate flood evacuations in Kibera, a densely populated informal settlement in Nairobi. Although data quality limits some of the model’s potential, the results reproduce patterns of observed behaviour. Evacuation shelters in the Northwest, North, and Northeast are shown to perform best. A major exit route to the South, a bridge crossing, and a river path are shown to be especially prone to congestion during evacuations. This paper reports on the first application of an agent-based model to an informal settlement, Kibera. The demonstration is an important step towards an operational tool for flood incident management planning in informal settlements around the world.